The implementation of a system of CardioQVARK to personalize treatment in terms of the digital ecosystem healthcare formation - V. Isaenko; M. Rybina (Цифровая социология)
In the terms of formation of new economy, consumption becomes an indicator of quality of life and socio-economic potential of the State and society. Within the framework of the development of the digital ecosystem healthcare major focus is personalizing treatment of humans, which aims to improve the quality of life and human life expectancy. Personalizing treatment has great socio-economic sense, since it is connected with the fact that the modern consumer emerging quality associated with digital technology. Russian scientists and representatives of technology entrepreneurship do not stand aside from the immediate task of building a digital economy in our country. LLC “Kardiokvark” developed and introduced into practice of domestic health care system CardioQVARK, which is a breakthrough digital technology in cardiology. This team feels as its goal system implementation into the daily life of the person a tool for early diagnosis of cardiovascular disease and all possible risks associated with this disease, including factors leading to the development of tuberculosis. Testing and expert assessment practitioners showed that portable CardioQVARK system has a great potential in registration records electrocardiograms using a portable CardioQVARK monitor with data transmission on the Internet of a mobile operator through cloud service in annex CardioQvark Doctor. Development and application in the practice of everyday life CardioQVARK system shows and identifies a number of common socio-economic problems and risks in the digital economy. So, digital economy puts ethical problems that pulls in a discussion about the im-plications of the implementation of the digital economy, a wide range of specialists in ethics, sociology, economics, history, philosophy, law, theology, and psychology. Acute and ambiguous problem becomes a problem of employment and structural unemployment; the issue of redeployment and creating new jobs on a global scale within the State and region; the problem of intelligence potential migration. Institutional support, strengthening the role of intangible assets, such as design, close attention by the State for production of small enterprise, lifelong learning-these are the challenges that need to be meet the requirements of the new economy.